The impact of the Roman Empire on the cult of Asclepius - Ploeg, Ghislaine van der (Impact of empire, 2018)
Mobility and connectivity in the cult of Asclepius -- Asclepius before the Roman Imperial Period -- Imperial relations with Asclepius -- Asclepius and the army -- The cult(s) of Asclepius in Roman North Africa